Simulation study on behaviour of reinforced concrete beam with various sizing and shape of opening in shear zone - Chong, Khang Zen (2018)
Every building need to include pipes and ducts for the installation of mechanical and electrical services. By creating an opening at the reinforced concrete beam can provide a passage to install all of these pipes and ducts. However, the effects of creating an opening at the reinforced concrete beam have to be studied in order to prevent the failure of the beam. The aim of this study is to determine the effect of various size of circular opening and different shapes of openings on the shear zone of reinforced concrete beam in terms of ultimate load, deflection and cracking. Ansys 12.0 was used in this study to simulate 4 point loading test on a total of 6 beams. A solid reinforced concrete beam named as RCB S. Three beams with different size of circular opening in diameter which is 60mm, 80mm and 100mm, labelled as RCB 1, RCB 2 and RCB 3 respectively. The other 2 beams with rectangular opening and square opening designated as RCB 4 and RCB 5 respectively. The opening size of different shapes of opening was equivalent to the size of a 100mm circular opening. All beams have identical cross section of 120mm X 300mm X 2000mm and the reinforcement arrangement unchanged. Based on the result, inclusion of a circular opening with diameter larger than or equal to 0.27 of the beam depth will reduce the ultimate load capacity by at least 21% while the mid-span deflection decrease by at least 64%. Besides that, in this study the optimum shape for opening is rectangular opening as it has the highest ultimate load. However, openings with sharp corners causes stress to be concentrated at the area which leads to early cracking to occur. In conclusion, the diameter of circular opening less than or equal to 0.2 depth of the beam will remain the behaviour of a solid reinforced concrete beam.